Effect of blood pressure variability on hypertensive retinopathy - Lei Jiao; Chaoran Lv; Hongling Zhang (Clinical and Experimental Hypertension, 2023)
Purpose This study intends to investigate the correlation between blood pressure variability (BPV) levels and the use of optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) to measure retinal microvasculature in hypertensive patients. Methods All individuals in the study had 24-hour ambulatory blood pressure monitoring and bilateral OCT and OCTA exams, and only data from the right eye were analyzed statistically. Results The study included 170 individuals, with 60 in the control group. The experimental group was separated into two groups based on the average real variability (ARV) median, with 55 in the low ARV group and 55 in the high ARV group. The mean thicknesses of the Retinal Nerve Fiber Layer (RNFL), internal limiting membrane-retinal pigment epithelial cell layer (ILM-RPE), vessel density (VD), and perfusion density (PD) in the high-ARV group were substantially lower in the low-ARV and control groups (p＜0.05). Multiple linear regression analysis revealed that disease duration, age, and 24 h diastolic standard deviation all affected RNFL mean thickness (p＜0.05). VD and PD were influenced by disease duration, systolic-ARV, daytime systolic blood pressure, intraocular pressure(IOP), and best-corrected visual acuity (BCVA) (p＜0.05). And the change in VD was connected to best-corrected visual acuity. Conclusion Hypertensive retinopathy is related to BPV. In clinical practice, we can assess the degree of BPV and retinopathy in hypertensive patients to track the progression of hypertension-mediated organ damage (HMOD). Correction of BPV may help treat or postpone the progression of HOMD.